(untitled) (Siddhajyoti Interdisciplinary Journal, 2022)
The Pandemic situation of COVID 19 had impacted the global education system leading to the cancellation of face-to-face classes and exams. Online classes had been started in universities and campuses on a large scale as an alternative to face-to-face education. The objective of the study was to find out the perception and practice of online teaching among students on public campuses in Nepal. The study was quantitative research design with survey methods. A Google online survey was conducted in response in which 402 respondent students of public campuses of Lumbini province were taken as a sample. The study found that the COVID-19 has resulted in public campuses shut all across the country so education has changed dramatically, with the distinctive rise of online learning, and started remotely on digital platforms. For this situation, the students are needed to adopt online learning. The majority 63% of students have been learning online during this pandemic situation. Online education is the best alternative of face to face learning as it is flexible, innovative, and interesting. Challenges like slow internet, shortage of adequate teaching materials, teachers’ disinterest, unstable power, and unavailability of devices were also found for conducting online courses.